An analysis of consumer perception and buying behaviour amongst millennial pet owners seeking out luxury pet products and services in Cape town - De Robillard, Sylvann (The IIE, 2022)
The pet industry is experiencing substantial growth as more people start to own pets. The role that pets play in society today has changed considerably and pets are being increasingly considered as a part of the family. Despite the growth in the pet industry, very little is known in terms of what motivates pet owners to purchase certain pet products and services or how to strategically market to them. It was identified that attachment influences the type of relationship owners, and pets have. Findings revealed that pet owners with a high level of attachment to their pets chose to purchase luxury pet products and services. This is particularly true for millennials pet parents. In addition, findings pointed to social media as the best platform to market to millennial pet owners through the use of messaging that is authentic in order to resonate with them. Data was collected by qualitative means in the form of one on one in-depth interviews along with data that was gathered from an online survey. The data collection and analysis methods that were used were chosen because they align with the research goal/s and the research question/s for this study. The anticipated contribution is to potentially influence and / or improve practice within the luxury pet product and services industry,
Keywords: Customer behaviour; Buying patterns; Millennials; Pets